Hungarian Monitoring, 10 July 1988 . [Magyar rádiófigyelő], 1988. július 10 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Hundreds of thousands demonstrate in Lithuania - Gorbachev expected in Warsaw Domestic Affairs: - Károly Grósz gives statement t New York Times - Fasori high school, Budapest, can re-open - Transylvanian Hungarians - Conversation with historian Mihály Korom on the cult of personality Economy: - Hungarian American joint company formed to set up microwave telephone network Külpolitika: - Százezres tüntetés volt Litvániában - Gorbacsovot Varsóba várják Belpolitika: - Grósz Károly nyilatkozatot adott a New York Times-nak - Újra megnyílhat a Fasori-gimnázium - Erdélyi magyarok ügye - Beszélgetés Korom Mihály történésszel a személyi kultuszról Gazdaság: - Magyar-amerikai vegyesvállalat alakul mikrohullámú telefonhálózat létesítésére